„... das Unendliche im Endlichen gebären ...“ - Susanne Gödde (Flaubert: Revue Critique et Génétique)
The following contribution investigates the specific means of signification that Creuzer articulates for the categories ‘symbol’ and ‘myth’ in his Symbolik und Mythologie der alten Völker (Symbolism and Mythology of the Ancient Peoples). Three processes of signification can be distinguished: 1. the meaning of a myth or mythical figure is constituted by  postulating inter-religious relations, often with recourse to etymological or similar linguistic relations; and a previous truth or dogmatic system is inferred to lie ‘behind’ the narrative and its linguistic interrelations. In these cases, Creuzer locates the authentic religious meaning within those relations. 2. Meaning is constituted through the indexicality of a (primarily aniconic) image of a god, whereby the cult-image of a phallus (which, according to Creuzer, represents the letter of a natural language) emerges as a privileged signifier. 3. Meaning is constituted by an incongruence of form and content. In this case, the symbol, threatening to explode its form, contains an ecstatic component. In contrast to the classicist ideal of a self-contained and well-proportioned whole, this incongruence gestures towards an aesthetic of ugliness. All three processes can be understood as anti-classical, bound up in a romantic hermeneutic.